Relationship between tear film stability, dry eye symptoms, and night driving vision among Malaysian adults - Pui Juan Woi; Purani Pathmanathan; Selena Yi Han Sieh; Mohd Harimi Abd Rahman; Haliza Abdul Mutalib; Madhavendra Bhandari; Naufal Nordin; Wan Muhammad Hirzi Wan Din (PLoS ONE, 2025)
Background Dry eye disease, a prevalent condition globally, affects the quality of the tear film and, subsequently, vision, especially during visually demanding tasks like driving at night. This study aims to evaluate the relationship between tear film stability, dry eye symptoms, and self-reported difficulties in night driving among Malaysian adults. Methods: Ninety participants aged 18-40 years with at least one year of night driving experience were recruited. Tear film stability was assessed using non-invasive tear break-up time (NIBUT), while dry eye symptoms were measured with the Ocular Surface Disease Index (OSDI). Night driving vision difficulties were evaluated using the Vision and Night Driving Questionnaire (VND-Q). Results: Participants with shorter NIBUT (mean =  3.95 ±  1.32 s; median =  3.97 s, IQR: 2.87-5.03 s) reported significantly greater difficulties in night driving compared to those with normal NIBUT (mean =  9.80 ±  3.86 s; median =  8.23 s, IQR: 6.90-11.70 s) (p <  0.001). Similarly, participants with severe dry eye symptoms had higher VND-Q scores (mean rank =  76.75) compared to those with asymptomatic to moderate symptoms (mean rank =  35.68–44.03) (p <  0.001). Spearman’s correlation showed moderate negative associations between NIBUT (r =  -0.327), OSDI (r =  -0.538), and VND-Q scores. However, there was no significant correlation between NIBUT and OSDI score. Multiple regression analysis revealed that both NIBUT and OSDI significantly predicted the VND-Q score, explaining 43.2% of the variance (p <  0.001). Conclusions: The findings suggest that poor tear film stability and severe dry eye symptoms contribute to night driving difficulties. Future studies should explore interventions aimed at improving tear film stability and dry eye symptoms to enhance driving safety at night.